2013
DOI: 10.1111/jpc.12157
|View full text |Cite
|
Sign up to set email alerts
|

Changes in longer consultations for children in general practice

Abstract: There have been significant changes in the patterns of longer consultations provided to children by GPs. Efforts to ensure that children receive primary care for chronic conditions and preventive care must now take on a greater urgency for the health-care system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 5 publications
0
23
0
Order By: Relevance
“…Yet the results from our study indicated that some CALD parents experienced that GPs did not ask questions about their child’s development. The difficulties faced by some parents with time constraints of their GPs is valid, as there are recent trends indicating a reduction in longer consultations provided for children at primary care practices in Australia [45]. This is particularly important as the delivery of quality primary care health service to a CALD population needs to incorporate an interpreter resulting in longer consultations [46].…”
Section: Discussionmentioning
confidence: 99%
“…Yet the results from our study indicated that some CALD parents experienced that GPs did not ask questions about their child’s development. The difficulties faced by some parents with time constraints of their GPs is valid, as there are recent trends indicating a reduction in longer consultations provided for children at primary care practices in Australia [45]. This is particularly important as the delivery of quality primary care health service to a CALD population needs to incorporate an interpreter resulting in longer consultations [46].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that doctors spend less time today with patients compared to the past. For example, comparing data from 1996 and 2010, the absolute number of longer consultations for children in Australia has decreased [35]. The declining negative evaluation of the personal qualities of doctors may also be a function of changes in attributional power.…”
Section: Discussionmentioning
confidence: 99%
“…10 Children with chronic illness are seen even less in the community. 11 The ability to maintain teaching standards outside of specialist paediatricians is increasingly problematic. Conversely, the increasing subspecialisation in children's hospitals can result in limiting exposure to the more common childhood conditions and more difficulty in focussing on the key curricula agenda described.…”
Section: Critical Thinking and Process Skillsmentioning
confidence: 99%